Distribusi dan Efektivitas Aksi Teknis dalam Sepak Bola Cerebral Palsy: Analisis Notasi Piala Asia-Oseania IFCPF - Susanti Susanti; Mohammad Furqon Hidayatullah; Fadilah Umar (Indonesian Journal of Physical Education and Sport Science, 2026)
Study purpose. This study aimed to analyze the distribution and effectiveness of technical actions performed by players during CP Football matches using a notational analysis approach. Materials and methods. The participants were 16 players (avg. age ± SD, 28.19 ± 5.56) from the Indonesian National Cerebral Palsy Football team who competed in the IFCPF Asia-Oceania Cup held in Surakarta, Indonesia, from 16–22 November 2025. A total sampling technique was applied. The unit of analysis was not individual players but technical actions occurring during matches. Match videos from four official games (Australia, Japan, Thailand, and Iran) were systematically observed to record four technical actions: passing, ball control, dribbling, and shooting. Each action was classified as successful or unsuccessful and analyzed using descriptive statistics to determine frequency, distribution, and effectiveness. Results. The results showed that passing was the most dominant technical action with 984 occurrences (44.3%) and a 90.5% success rate, followed by ball control with 847 occurrences (38.1%) and an 89.0% success rate. Dribbling accounted for 271 occurrences (12.2%) with a 67.9% success rate, while shooting was the least frequent action with 123 occurrences (5.5%) and a 35.8% success rate. In addition, most technical actions were predominantly performed using the right foot. Conclusions. The findings indicate that match performance in CP Football is largely characterized by ball possession and circulation through passing and ball control, while penetrating and finishing actions occur less frequently and with lower effectiveness. Training programs should therefore emphasize passing accuracy, ball control skills, and bilateral technical development to enhance players’ performance in competitive matches.